HER-2 positive breast carcinoma associated pathological characteristics - González-Müller, Carlos (2005)
Objective: To determine the prevalence and associated characteristics of HER-2 overexpression in infiltrative primary breast cancer. Materials and Methods: From October through December 2003 and from May through December 2004, 274 cases of infiltrative primary breast carcinoma were studied and pathological characteristics correlation with HER-2 overexpression 3+ was determined at Edgardo Rebagliati Martins National Hospital’s Pathological Anatomy Department. Results: Three plus HER-2 overexpression was found in 64 (23,4%) cases, 2+ in 9 (3,3%) and negative (1+ or 0) in 201 (73,4%) cases. The non-specified infiltrative ductal histology type was present in 211 (77%) cases, and the infiltrative lobulillar in 27 (9,9%). We determined associated 3+ overexpression in non-specified infiltrative ductal carcinoma (p=0,0001), nipple Paget’s disease (p <0,0001), and when estrogen receptors tumor expression was absent (p <0,0001). Only the absence of estrogen receptors expression was an independent associated characteristic (p <0,0001). Conclusions: The prevalence of 3+ overexpression occurred in 23,4% of the cases, and the associated characteristics were the non-specified infiltrative ductal histology type, nipple Paget’s disease, and the absence of estrogen receptors expression.